The Role of Automation and IoT in Enhancing Operational Efficiency: Evidence from PLS-SEM Analysis - Suhandi; Purnama, Suryari; Ahsanitaqwim, Ridhuan; Nurm, Sirje (APTISI Transactions on Management (ATM), 2025)
In today's competitive business environment, operational efficiency is crucial for organizations to maintain a competitive edge. The integration of automation and the Internet of Things (IoT) has emerged as a transformative approach to streamline processes and enhance productivity. However, the synergistic impact of these technologies on operational efficiency remains underexplored. This study aims to evaluate the individual and combined effects of automation and IoT on operational efficiency. It seeks to provide empirical evidence on how these technologies contribute to optimizing workflows and decision-making processes. Methodology Using Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from organizations across multiple industries. Constructs were measured through validated survey instruments, and hypotheses were tested for direct and synergistic effects. The findings indicate that automation significantly enhances operational efficiency by reducing errors and improving process consistency. IoT adoption complements this by enabling real-time insights and improved decision-making. The combined implementation of these technologies demonstrates a moderate synergistic effect, amplifying operational gains. This study underscores the transformative potential of integrating automation and IoT. By leveraging their complementary strengths, organizations can achieve higher levels of efficiency, providing valuable guidance for digital transformation strategies. In today's competitive business environment, operational efficiency is crucial for organizations to maintain a competitive edge. The integration of automation and the Internet of Things (IoT) has emerged as a transformative approach to streamline processes and enhance productivity. However, the synergistic impact of these technologies on operational efficiency remains underexplored. This study aims to evaluate the individual and combined effects of automation and IoT on operational efficiency. It seeks to provide empirical evidence on how these technologies contribute to optimizing workflows and decision-making processes. Methodology Using Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from organizations across multiple industries. Constructs were measured through validated survey instruments, and hypotheses were tested for direct and synergistic effects. The findings indicate that automation significantly enhances operational efficiency by reducing errors and improving process consistency. IoT adoption complements this by enabling real-time insights and improved decision-making. The combined implementation of these technologies demonstrates a moderate synergistic effect, amplifying operational gains. This study underscores the transformative potential of integrating automation and IoT. By leveraging their complementary strengths, organizations can achieve higher levels of efficiency, providing valuable guidance for digital transformation strategies.